Hemoglobinas anormales en la población neonatal de Costa Rica - Abarca, Gabriela; Navarrete, Marta; Trejos, Rafael; de Céspedes, Carlos; Saborío, Manuel (Revista de Biología Tropical, 2008)
Hemoglobinopathies are hereditary autosomic recessive diseases. A total of 70 943 samples of whole blood collected by heel prick in filter paper (S&S 903) from throughout Costa Rica (October 2005-October 2006) were analyzed to detect vari-ants of hemoglobin by the iso-electric focusing technique. Eight hundred ninety one cases presented some vari-ant, for a frecuency of 1/79. Five cases are homozygous for hemoglobin S (sickle cell disease) and one shows the double heterozygous genotype SC. in this study the S and C variants of hemoglobin, although with some local differences, are widespread all over the country. Thus, the prevention of new cases is important through the test-ing of hemoglobin in the Costa Rican National Newborn Screening Program, together with a interdisciplinary National Program of Education for the disease and carrier status (AS/AC) for patients, families and medicar personnel. This is the basis for proper genetic counseling, to improve treatment and to reduce morbi-mortality.